A multi-objective EBCO-TS algorithm for efficient task scheduling in mobile cloud computing. (6th April 2020) - Arun, C.; Prabu, K.
Cloud computing proposals a novel service to the users to permitting for consume the distant resources due to some faults faced in smart devices. This causes to the emergence of the newest computing model known as mobile cloud computing. It supports to the user that the mobile devices not require to execute the application in user device as a replacement of some jobs will be execute in distant cloud/cloudlet is named as offloading jobs which is the nearby to the device. At the similar time job scheduling is more critical commonly at both the mobile devices and the mobile cloud. To solving the task scheduling problem, we propose an EBCO-TS algorithm for priority based task scheduling with load balancing model. The proposed EBCO-TS consume the power only 85% compared to the existing methods and it shows better load balancing when the number of request increases in the cloudlet.